2014
DOI: 10.17219/acem/37217
|View full text |Cite
|
Sign up to set email alerts
|

The Distribution of Beta Lactamase Genes in Escherichia Coli Phylotypes Isolated from Diarrhea and UTI Cases in Northwest Iran

Abstract: Background. Pathogenic Escherichia coli strains are a common cause of intestinal and extra-intestinal infections, especially in developing countries. Extended spectrum beta-lactamases (ESBL S ), a heterogeneous group of plasmidencoded beta-lactamases, are common throughout the world. Objectives. The aim of the present study was to determine the phenotypic and genotypic characteristics of ESBL S produced by E. coli isolates taken from patients with diarrhea and urinary tract infections (UTI) in northwest Iran. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 20 publications
0
3
0
Order By: Relevance
“…Treating infections in LMICs adequately is challenging, because of the increasing resistance to first line treatments. This is due to the extended use and misuse of antibiotics [ 14 – 15 ],[ 28 ], the prohibitive costs in such settings of alternative choices such as cephalosporins [ 29 ] and the limited antibiotic stock available in these areas [ 30 ]. Our isolates showed remarkably low antimicrobial resistance levels compared to ExPEC isolates from other studies carried out in several African countries [ 14 – 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Treating infections in LMICs adequately is challenging, because of the increasing resistance to first line treatments. This is due to the extended use and misuse of antibiotics [ 14 – 15 ],[ 28 ], the prohibitive costs in such settings of alternative choices such as cephalosporins [ 29 ] and the limited antibiotic stock available in these areas [ 30 ]. Our isolates showed remarkably low antimicrobial resistance levels compared to ExPEC isolates from other studies carried out in several African countries [ 14 – 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…Based on our comprehensive search, 28 studies with eligibility criteria (Figure 1) were included in the meta-analysis (Ramos et al, 2011;Navidinia et al, 2013;Adib et al, 2014;Alizade et al, 2014a;Alizade et al, 2014b;Hemati et al, 2014;Kazemnia et al, 2014;Derakhshandeh et al, 2015;Iranpour et al, 2015;Rahdar et al, 2015;Salmani et al, 2016;Sohrabi and Zeighami, 2016;Hashemizadeh et al, 2017;Hojabri et al, 2017;Salehzadeh and Zamani, 2018;Bahadori et al, 2019;Farajzadah Sheikh et al, 2019;Norouzian et al, 2019;Shahin et al, 2019;Staji et al, 2019;Bakhtiari et al, 2020;Moez et al, 2020;Ranjbar et al, 2020;Yazdanpour et al, 2020). Of the 28 included studies, 17 and 9 studies reported the prevalence of phylogenic groups from hospitalized and community patients, respectively.…”
Section: Database Search and Characterization Of Studiesmentioning
confidence: 99%
“…Pathogenic strains of E. coli are considered as one of the most important causes of gastrointestinal and non-gastrointestinal infections. It also causes a wide range of extraintestinal infections such as urinary tract infection (UTI), septicemia, neonatal meningitis and infections of the central nervous system that leads to mortality and increased cost of treatment (2,3). Among the clinical isolates that produce extendedspectrum β-lactamases (ESBL) enzymes, the members of the family Enterobacteriaceae, particularly E. coli show resistance against βlactam antibiotics.…”
Section: Introductionmentioning
confidence: 99%